Gene Therapy - Giacca, Mauro; SpringerLink (Online service) (Milano : Springer Milan, 2010)
This book presents to the reader a comprehensive and detailed, yet easily accessible, description of the whole field of gene therapy. It covers topics ranging from vector development to the results of the most recent clinical trials. It includes descriptions of lentiviral and AAV vector development, of therapeutic gene selection (including siRNAs, shRNAs, and microRNAs), and of the most recent clinical applications of gene therapy for diseases of the eye, the cardiovascular system, and the central nervous system. Of note, the book only considers conditions for which transfer of genetic material has already progressed to clinical applications or is close to doing so. The language is plain and, whenever possible, non-technical. Since the book is intended to be a textbook in the field of gene therapy in both the basic science and clinical fields, whenever technical descriptions are required these are provided. Readers will include graduate students in the life sciences area in their final years of study, PhD students, and medical doctors specializing in different fields of internal and specialist medicine, in addition to research scientists working in various areas of current biomedical research.
to Gene Therapy -- Therapeutic Nucleic Acids -- Methods for Gene Delivery -- Clinical Applications of Gene Therapy -- Ethical and Social Problems of Gene Therapy.
Keywords: Medicine; Gene therapy; Medical virology; Genetic engineering; Internal medicine; Biomedicine; Gene Therapy; Molecular Medicine; Internal Medicine; Genetic Engineering; Virology